2013
DOI: 10.1186/gm471
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome DNA/RNA sequencing identifies truncating mutations in RBCK1 in a novel Mendelian disease with neuromuscular and cardiac involvement

Abstract: BackgroundWhole-exome sequencing has identified the causes of several Mendelian diseases by analyzing multiple unrelated cases, but it is more challenging to resolve the cause of extremely rare and suspected Mendelian diseases from individual families. We identified a family quartet with two children, both affected with a previously unreported disease, characterized by progressive muscular weakness and cardiomyopathy, with normal intelligence. During the course of the study, we identified one additional unrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 31 publications
0
93
0
Order By: Relevance
“…Given that HOIP levels were lower in interferon-treated cpdm keratinocytes than in WT keratinocytes, augmented activation of antiapoptotic NF-B mediated by an increase in HOIL-1L/HOIP-containing LUBAC might not be able to completely override the augmented cell death caused by loss of SHARPIN. Some humans lacking HOIL-1L, however, exhibit autoinflammation and immunodeficiency in addition to amylopectinosis in early childhood (30), whereas in other cases, mutations in the HOIL-1L gene cause various degrees of myopathies without immunological symptoms beginning in childhood or the juvenile years (39,41). We have not observed any overt inflammatory diseases in HOIL-1L KO or HOIL-1L Ϫ/Ϫ SHARPIN ϩ/cpdm mice, at least by 12 weeks of age ( Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Given that HOIP levels were lower in interferon-treated cpdm keratinocytes than in WT keratinocytes, augmented activation of antiapoptotic NF-B mediated by an increase in HOIL-1L/HOIP-containing LUBAC might not be able to completely override the augmented cell death caused by loss of SHARPIN. Some humans lacking HOIL-1L, however, exhibit autoinflammation and immunodeficiency in addition to amylopectinosis in early childhood (30), whereas in other cases, mutations in the HOIL-1L gene cause various degrees of myopathies without immunological symptoms beginning in childhood or the juvenile years (39,41). We have not observed any overt inflammatory diseases in HOIL-1L KO or HOIL-1L Ϫ/Ϫ SHARPIN ϩ/cpdm mice, at least by 12 weeks of age ( Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Homozygous or compound heterozygous RBCK1 mutations are associated with early onset of disease, which includes polyglucosan accumulation in several tissues, skeletal myopathy, and rapidly progressing cardiomyopathy (Boisson et al, 2012;Nilsson et al, 2013;Wang et al, 2013). Two distinct phenotypes have been described.…”
Section: Clinical and Morphological Characteristicsmentioning
confidence: 98%
“…While our study identified an unexpected noncoding mutation in a novel disease gene, several prior studies have also shown the potential of RNA-seq for discovering splicing perturbations in known human disease genes (Chandrasekharappa et al 2013), splicing defects caused by variants in canonical (i.e., predictable) splice sites of genes not previously associated with disease (Wang et al 2013), fusion transcripts in cancer (Pierron et al 2012;Morin et al 2013), and RNA-seq confirmation of known transcription-altering mutations from genetic screens in model organisms (Miller et al 2013). These studies also identified decreased transcript levels due to nonsense-mediated decay and other unexpected splice defects such as missense and synonymous exonic mutations causing exon skipping (Chandrasekharappa et al 2013;Miller et al 2013).…”
Section: A Transcriptomic Approach Facilitates the Discovery Of Variamentioning
confidence: 99%